Gen Z's Perspective: Unveiling the Impact of Emotion and Cognitive in Shaping Customer Experience in Omnichannel Context - Nur Hidayati; Rahmawati (International Journal of Social Science and Business, 2023)
Generation Z (Gen Z) exhibits unique characteristics in online activities, primarily through the use of social media for inspiration, product research, and interaction with favorite brands. To support this behavior, this study aims to analyze knowledge about customer experience in an omnichannel context by involving Gen Z and has involved cognitive, emotional, loyalty intention and purchase intention. This study used purposive sampling techniques to collect research participants. A total of 421 respondents met the criteria and hypotheses were tested using Smart PLS. These findings reveal that emotions have a direct effect on purchase intent, so cognitive has a direct effect on loyalty intent. In addition, emotions and cognitive also have a significant effect on E-WOM. E-WOM can also be partially mediated by the emotional and cognitive effects on purchase intent and loyalty. Gen Z is very accustomed and aware of omnichannel existence because of their familiarity with internet activities. Many Gen Z individuals see social media not only as a means of connectivity but also as a platform to seek inspiration, research products, and connect with their favorite brands. Overall, the study identifies omnichannel strategies as key to understanding and meeting the needs of Gen Z consumers, providing valuable insights for companies in improving consumer engagement and loyalty.